Pengaruh Metode Pembelajaran Mind Mapping terhadap Hasil Belajar pada Pokok Bahasan Hukum-Hukum Dasar Kimia Siswa Kelas X Semester Ganjil di SMA Negeri 2 Langowan - Frindly Makarawung; I Dewe Ketut Anom; John Lombok (Oxygenius Journal Of Chemistry Education, 2019)
This research aims to determine the effect of mind mapping learning methods on the basic laws of chemistry toward learning outcomes of students of class X MIPA in SMA Negeri 2 Langowan. The sample used in this study were all students of class X MIPA of SMA Negeri 2 Langowan. This research uses an experimental method, with the research method used is Quasi Experiment with Nonequivalent Control Group Design design. The research data were obtained from post-test results. Obtained the average value of student learning outcomes Experiment class is 85. The results showed the value of tcount = 15.7> ttable = 2.21, so H0 was rejected and H1 was accepted. Based on the results of the research it can be concluded that there is an influence on student learning outcomes on the basic laws of chemistry using mind mapping learning methods.